ANY QUALITY POLICY AND THE RIGHT TO FOOD: A STUDY OF THE STATE’S CONSTITUTIONAL OBLIGATIONS - Isharyanto Isharyanto; Deva Mahendra Caesar Bimantya (Law Faculty of Universitas Bandar Lampung, 2026)
This study examines the any quality policy in government paddy procurement as a state response to the need to maintain national rice availability, while raising concerns regarding the protection of food quality as an integral component of the right to food. The core issue lies in the tension between flexibility in absorbing paddy from farmers and the state’s legal obligation to provide food that is safe, suitable, and of adequate quality in accordance with the relevant regulatory framework. The research employs a doctrinal method using primary and secondary legal materials, combined with statutory, conceptual, and comparative approaches that include policy practices in India, China, and Thailand, in order to assess the alignment of the policy with the principles of the right to food and proportionality. The findings indicate that the any quality policy can meet constitutional obligations only when supported by adequate quality control mechanisms. Price instruments such as rafaksi are insufficient to preserve quality and therefore must be complemented by strengthened post harvest facilities, technical standards for drying and sorting, consistent quality monitoring, and enhanced administrative capacity at both national and regional levels. The study concludes that an integrated policy design linking price instruments with technical instruments is essential to ensure that the state can effectively safeguard food quality and fully uphold the right to food.